Vitamin D supplementation vs. placebo and incident type 2 diabetes in an ancillary study of the randomized Vitamin D and Omega-3 Trial - Tobias, Deirdre K.; Pradhan, Aruna D.; Duran, Edward K.; Li, Chunying; Song, Yiqing; Buring, Julie E.; Cook, Nancy R.; Mora, Samia; Manson, JoAnn E. (Nature communications, 2025)
Observational and experimental evidence suggests that vitamin D plays a role in type 2 diabetes (T2D). However, prior randomized supplementation trials are limited to high-risk patients with prediabetes. Here we aim to evaluate whether vitamin D supplementation reduces risk of T2D in a general population of older US adults. The study design is an ancillary analysis (VITAL-T2D) of The Vitamin D and Omega-3 Trial (VITAL), a completed randomized, double-blind, placebo-controlled 2 × 2 trial of daily vitamin D 3 (cholecalciferol; 2000 IU/day) and omega-3 fatty acids (1 g/day) for the primary prevention of cancer and cardiovascular disease. We also conducted a systematic review and meta-analysis of vitamin D trial (≥1000 IU/d cholecalciferol) vs. placebo and T2D risk. We analyzed 22,220 adults with mean age 67.2 years (SD = 7.1) without T2D at enrollment (2011 to 2014), randomized to vitamin D 3 or placebo. Mean body mass index (BMI) was 27.5 kg/m 2 (SD = 5.3), with 51% female and 17% Black race/ethnicity. A subcohort ( n = 911) attended in-person visits at baseline and 2 years for glycemic trait analyses. Our meta-analysis included 3 additional trials (5205 participants; 936 T2D cases). The primary outcome for the VITAL-T2D is intention-to-treat effect of vitamin D vs. placebo for incident T2D. T2D incidence (cases/1000py) at median follow-up of 5.3 y was 3.98 for vitamin D and 4.37 for placebo (hazard ratio [HR] = 0.91; 95% confidence interval [CI] = 0.76, 1.09). Results did not differ by age, sex, BMI, or baseline 25-hydroxyvitamin D, and vitamin D had no effect on glycemic traits at 2 years. Meta-analysis of 4 trials ( n = 5205; 936 T2D cases) obtained HR = 0.89 (CI = 0.80, 0.99). In conclusion, Vitamin D supplementation did not reduce T2D in older US adults, but a modest reduction was observed when meta-analyzed with prior trials. Trial Registration : ClinicalTrials.gov #NCT01633177. Systematic Review Registration : PROSPERO #CRD42019147562. Observational and experimental evidence suggests that vitamin D plays a role in glycemic control. Here, the authors report that in an ancillary study of the placebo-controlled randomized VITAL trial there is no effect of 2000 IU/day of vitamin D supplementation over 5 years on the prevention of type 2 diabetes in 22,220 older US adults.